Microbial Surface Treatment of Sand with Sporosarcina pasteurii to Improve the Wind Erosion Resistance in Urmia Lake - Hooshang Katebi; Ahmad Fahmi; Ahad Ouria; Alireza Babaeian Amini; Hossein Samadi Kafil (Applied and Environmental Soil Science)
Background. In this research, the potential of the microbially induced carbonate precipitation method for the surface treatment of sand samples of Jabal Kandi dunes, located in the adjacency of Urmia Lake in the northwest of Iran, was considered. Methods. Sporosarcina pasteurii was used as ureolytic bacteria for the preparation of the microbial solution. Corn steep liquor containing urea was used as an inexpensive growth media. The effects of the concentration of cementation solution and the number of treatment cycles were considered. Because of the presence of some hydrolyzed urea in the prepared microbial suspension, two methods of treatment, i.e., the mixed and separate addition of microbial solution and cementation solution to the sand surface, were investigated. Penetration and erosion resistance of the microbial treated sand (sand crust) were measured using a handheld penetrometer and a wind tunnel system. Results. The results showed that the penetration and erosion resistance of the treated sand samples via microbial-induced carbonate precipitation method were improved significantly. In the method with the separate addition of microbial and cementation solutions to the sand surface, a stable sand crust was created on top of the sand. Discussion. This study tried to optimize the microbial application of Sporosarcina pasteurii for surface treatment of sand via microbial-induced carbonate precipitation. Significant and results showed that this method can be used on the field scale for the stabilization of sand dunes. The advanced biotechnology application of this bacterium can be used as an environmentally friendly and safe method instead of other methods.